Computer science applied to competitive swimming: Analysis of swimming performance and fluid mechanics - Arellano, R. (International Journal of Computer Science in Sport, 2003)
The purpose of our paper is to show how computer science is helping to develop knowledge of swimming sport. Two samples are used in this paper: the analysis of swimming competition and the fluid mechanics applied to swimming. Methods and variables are defined to perform the analysis of competition showing the statistical approaches used to study the relationships with the performance. Methods of flow visualization and their applicability to study the swimming propulsion are detailed. New technologies and computer science seem to contribute to the understanding how human beings perform in the water. Automatic data collection during swimming competition will allow us to know how they win or lose the races and to monitor the training process. The analysis of flow behavior around the swimmer`s body and propulsive limbs applying flow visualization and PIV enables energy interchange between water and human body to be measured.